2019
DOI: 10.1186/s12889-019-7027-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise for prevention of dementia (EPD) study: background, design and methods

Abstract: Background Several observational studies have shown that exercise reduces the risk of cognitive decline; however, evidences from long-term, well-conducted, randomized controlled trials are scanty. The principal aim of this study is to verify whether a long-term program of multimodal supervised exercise improves the cognitive function and/or reduces the rate of cognitive decline in older adults at different degrees of risk for dementia. Methods/design EPD is a parallel g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 57 publications
0
15
0
6
Order By: Relevance
“…Unemployed elderly might be less physically active than their employed counterparts. Exercise has a direct effect on preserving neurogenesis and favoring neuroplasticity [23]. Studies have reported an association of physical exercise with a decreased risk of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Unemployed elderly might be less physically active than their employed counterparts. Exercise has a direct effect on preserving neurogenesis and favoring neuroplasticity [23]. Studies have reported an association of physical exercise with a decreased risk of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Among trials with physical activity as the only intervention, improved cognition was reported in patients with mild AD after 16 weeks of exercise [7], whereas no cognitive effects were seen in demented patients after 12 months [8]. An ongoing trial with a 2-year exercise intervention will provide further information if physical exercise can be beneficial in preventing dementia [9]. As summarized in reviews and meta-analyses, findings from previous prospective cohort studies differ but pooled results indicate protective effects [1014].…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente la evidencia científica disponible demuestra que la actividad física no solo trae consigo una gran cantidad de beneficios al estado físico general (y cardiovascular en particular), sino que también provoca beneficios en la salud mental de las personas al aliviar el estrés, mejorar el sueño, regular el estado anímico, aumentar el interés en el sexo y reducir el cansancio, aumentando el estado de alerta [48][49][50][51][52][53]. También sabemos que sirve de factor protector para algunas enfermedades neurológicas como las demencias [54][55][56][57][58] y la integración sistemática de comportamientos saludables coherentes con el envejecer generativamente [59].…”
Section: Discussionunclassified